Effects of mineralogy, chemistry and physical properties of basalts on carbon capture potential and plant-nutrient element release via enhanced weathering. (September 2021) - Lewis, Amy L.; Sarkar, Binoy; Wade, Peter; Kemp, Simon J.; Hodson, Mark E.; Taylor, Lyla L.; Yeong, Kok Loong; Davies, Kalu; Nelson, Paul N.; Bird, Michael I.; Kantola, Ilsa B.; Masters, Michael D.; et al.
Abstract: Mafic igneous rocks, such as basalt, are composed of abundant calcium- and magnesium-rich silicate minerals widely proposed to be suitable for scalable carbon dioxide removal (CDR) by enhanced rock weathering (ERW). Here, we report a detailed characterization of the mineralogy, chemistry, particle size and surface area of six mined basalts being used in large-scale ERW field trials. We use 1-D reactive transport modelling (RTM) of soil profile processes to simulate inorganic CDR potential via cation flux (Mg 2+, Ca 2+, K + and Na + ) and assess the release of the essential plant nutrients phosphorus (P) and potassium (K) for a typical clay-loam agricultural soil. The basalts are primarily composed of pyroxene and plagioclase feldspar (up to 71 wt%), with accessory olivine, quartz, glass and alkali feldspar. Mean crushed particle size varies by a factor of 10, owing to differences in the mining operations and grinding processes. RTM simulations, based on measured mineral composition and N2 -gas BET specific surface area (SSA), yielded potential CDR values of between c. 1.3 and 8.5 t CO2 ha −1 after 15 years following a baseline application of 50 t ha −1 basalt. The RTM results are comparative for the range of inputs that are described and should be considered illustrative for an agricultural soil. Nevertheless, they indicate that increasing the surface area for slow-weathering basalts through energy intensive grinding prior to field application in an ERW context may not be warranted in terms of additional CDR gains. We developed a function to convert CDR based on widely available and easily measured rock chemistry measures to more realistic determinations based on mineralogy. When applied to a chemistry dataset for >1300 basalt analyses from 25 large igneous provinces, we simulated cumulative CDR potentials of up to c. 8.5 t CO2 ha −1 after 30 years of weathering, assuming a single application of basalt with a SSA of 1 m 2  g −1 . Our RTM simulations suggest that ERW with basalt releases sufficient phosphorus (P) to substitute for typical arable crop P-fertiliser usage in Europe and the USA offering potential to reduce demand for expensive rock-derived P. Highlights: Basalt is an abundant rock proposed to be suitable for enhanced weathering. We characterised the mineralogy and surface area of six commercial basalts. We used these characteristics in a reactive transport model of a cropland soil. Predicted CO2 removal ranged from 1.3-8.5 t CO2 ha -1 after 15 years of weathering.